A LIGHT-WEIGHT MVC (MODEL-VIEW-CONTROLLER) FRAMEWORK FOR SMART DEVICE APPLICATION - Laksana, Budi Darma; Ballangan, Cherry Galatia (Jurnal Informatika, 2006)
In this paper, a light-weight MVC framework for smart device application is designed and implemented. The primary goal of the work is to provide a MVC framework for a commercial smart device product development. To this end, the developed framework presents integration between the classic design patterns, MVC and state-of-the-art technology XAML by adapting a MVC framework of an open source XAML efforts, MyXaml into .NET Compact Framework. As the compact framework only comprises 12% of .NET Framework library, some design and architectural changes of the existing framework need to be done to achieve the same abstraction level. The adapted framework enables to reduce the complexity of the smart device application development, reuse each component of the MVC separately in different project and provide a more manageable source code as the system architecture is more apparent from the source code itself as well as provide a commonality of the development pattern. A prototype of simple database interface application was built to show these benefits.